Some Socio-Agricultural Changes as a Result of Introduction of Irrigation in A Desert Region - Bharara, L P; Malhotra, S P; Patwa, F C (Annals of Arid Zone, 2016)
Introduction of irrigation brought. changes in socio agricultural aspect.s of the beneficiaries and non-beneficiaries, all in the same desert. region-Rajasthan Canal Project Tehsil Gharsana, district Ganganagar, Compared with each other, socio-agricultural changes occurred in the occupational structure land use, land distribution pattern, size of land holding. area sown. yield, fallow land, agricultural inputs and labour employment. Traditional caste occupations shifted to cultivation and agricultural labour, subsistence farming gradually commercialised. mean size of land holding per household decreased, Landless class gradually became land owning class, agricultural inputs and demand for labour employment increased, and thus a new folk of farming communities sprang up.